Characteristics of blood glucose distribution in a health examination population in Sichuan (2009–2017). Issue 45 (6th November 2020) - Ding, Fei; Nie, Xin; Liao, Jing; He, Yong; Li, Guixing
Abstract : Abstract: The prevalence of diabetes mellitus and impaired fasting glucose is rapidly increasing in the recent years. Hyperglycemia associated atherosclerosis and other complications are posing a serious threat to human health. The present study aimed to analyze the blood glucose distribution characteristics within a large size of health examination population of Sichuan province, China. This was a retrospective study conducted in 878, 019 subjects (483, 914 males and 394, 105 females) aged more than 18 years old from the Health Examination Center at West China Hospital, Sichuan University during 2009 to 2017. The blood glucose levels were compared in different age groups and different years. The blood glucose levels were significantly increased in recent years. The percentage of cases with high glucose levels was significantly higher in males than that in females since 2009 to 2017. Moreover, the blood glucose levels and the percentage of high glucose levels in aged population were significantly higher than those in younger population every year. The health examination population showed increased percentage of blood glucose levels, and so regular physical examination and glucose control are highly important in aged population. Abstract : Supplemental Digital Content is available in the text